Aspectos de la biologia reproductiva del Ostrero Negro Haematopus ater en las Islas Isabel, Bahia Bustamante, Chubut - Punta, Gabriel; Herrera, Gonzalo; Saravia, José (El Hornero, 1995)
Este artículo no cuenta con un resumen.